Isolation and Characterization of Carbofuran - Degrading Bacteria from Malaysian Soil - Ariffin, Fazilah (2005)
Bacteria isolates isolated from soil samples were screened for the ability to degrade Carbofuran. One hundred and fifty isolates isolated from various locations in Selangor, Perak and Johor were screened for the ability to degrade Carbofuran. Five isolates gave positive results with varying degrees of degradation. Based on these results, bacterial Isolate 147 Pseudomonas sp. isolated from Bukit Ekspo Universiti Putra Malaysia (UPM) Selangor campus was selected for further studies due to its ability to completely degrade Carbofuran in the minimum amount of time. This bacterium grew on Carbofuran as a sole source of nitrogen in a minimal salts medium. It showed the ability to degrade Carbofuran present in the minimal salts medium containing 100 mgll Carbofuran as nitrogen source. MTT 13-(4,5-dimethyl-2- thiazoly1)-2,5 diphenyl tetrazolium bromide] assay was used to screen bacteria capable of degrading pesticides indicated by the change in colour of the tetrazolium salt from yellow to blue. This bacterium reduced the tetrazolium salt which act as on electron acceptor for the formation of blue formazan. The growth optimization of Isolate 147 was investigated under various conditions. Optimum growth was obtained at 30°C and pH 8 an additional carbon source such as glucose was needed to provide sufficient energy for the degradation to occur. It also grew abundantly in high concentration of 100mgIl Carbofuran. The degradation of Carbofuran by Isolate 147 was analysed using High Performance Liquid Chromatography (HPLC). This bacterium was able to degrade Carbofuran up to 93.03 % after six days incubation in the minimal salt medium. Enzyme produced by Isolate 147 during Carbofuran degradation was partially purified by 3.6 fold with ion exchange chromatography with an overall yield of 72.6%. It was shown to have a K, value of 448.5 pM, optimum activity at 30°C and pH 8.